Impact of Integrated Modular Pharmacology Curriculum on Undergraduate Medical Student’s Performance - Asma Inam, Muhammad Zahid Latif, Muhammad Atif Qureshi (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Continuous efforts to reform health profession are being exercised around the world through change in medical curriculum. Gradual shift of medical teaching towards integration of basic and clinical subjects is a need of time. However, the impact of this change on students’ performance is yet not defined completely. Aim: To compare pharmacology final professional result status & mean score of undergraduate medical students taught by integrated and conventional curriculum. Methods: This observational, cross-sectional study was conducted on 305 undergraduate medical students of Azra Naheed Medical College. Students who were educated& assessed by two different teaching system were enrolled. Result status and exam score of Final term examination in Pharmacology subject were noted and compared. Data were analyzed using SPSS 22.Chi-square test and was applied for statistical significance, and p-value <0.05 was considered significant. Results: The study reflects that 55% of students are male while 45% are female. Our study indicates statistically significant higher passing percentage and exam score of students belonging to integrated modular system compared to conventional teaching system i.e., (98% Vs 89%) and (204.98±1.45 vs 188.04 ±2.45). Also, the curriculum design and result status were significantly associated with each other (Pearson chi square P-value 0.003). Conclusion: Undergraduate medical students performed better under integrated modular system than conventional teaching. MeSH words: Integrated modular curriculum, Traditional medical curriculum, Assessment score, medical education,